THE USE OF SCIENCE LITERACY TAXONOMY TO MEASURE CHEMISTRY LITERACY OF THE SCIENCE TEACHER CANDIDATES - Hayati, Muriani Nur (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
Abstract ___________________________________________________________________ Mastery of scientific literacy is one of the objectives in science learning. Chemistry is one of the aspects of the material in science, so that control of chemical literacy is one indicator of the success of achieving success performance scientific literacy. This study aims to measure literacy levels of chemical science student teachers in the subject of Basic Chemistry. Ability scientific literacy of students that will be measured are to: 1) recognize chemical concepts (nominal literacy); 2) Describe the chemical concepts (functional literacy); 3) use their understanding of chemical concepts to explain a phenomenon (conceptual literacy); and 4) use their understanding of chemistry to analyze information from short paragraph (literacy multi-dimensional). This research is descriptive qualitative. Sampling was done by purposive random sampling technique. The sample (N= 61) was composed of first and second year in the Department of Science Education. Data collection techniques were questionnaires and open-ended paragraphs. The validity of the instrument used was expert judgment. Based on the research results, obtained the literacy skills of students by 56.64% nominal or category, please, and functional literacy of 26.40% or category Very Less. Meanwhile, conceptual literacy was 61.50%; multidimensional literacy was 50.20%. The low level of ability on functional literacy and multidimensional was because students are not accustomed to using asessment that revealed a high level thinking skills. These findings are expected to help in the design process of the new curriculum (KKNI) which put an emphasis on instructional strategies in developing chemical literacy.